The effects of process parameters on concentration of dragon fruit juices via freeze concentration technique - Ahmad Firdaus, Mohd (2012)
Dragon fruit is one of the most nutritious and exotic fruit that is available in Malaysia.In this research,dragon fruit juice was concentrated by using freeze concentration process.Concentrated fruit juice can be preserved longer than non concentrated fruit juice.Besides,due to its small capacity storage,concentrated fruit juice also can minimize the transportation cost to import or export it.Freeze concentration process was used because it eliminates water from the juice at temperature below the water’s freezing point,thus preserving the aromatic compound that originally contained in the fruit juice.In addition to research objective,two process parameters and its effect on the fruit juice final concentration were studied.The process parameters were stirring rate and cooling medium temperature.The apparatus used to done the freeze concentration process was crystallizer unit.Dragon fruit juice that was blended and standardized its initial concentration was put into the crystallization unit.The fruit juice spent 12 hours in the crystallizer unit.During the time spent in the crystallizer unit,stirring rate and cooling medium temperature were varied in the range of (600, 800, 1000, 1200 and 1400) rpm and (-6, -8, -10, -12 and -14) °C.To determine the best stirring rate,the temperature of the cooling medium in the crystallizer unit was constant at -10 °C while the stirring rate of the fruit juice was varied.Then,the best stirring rate was used to determine the best cooling medium temperature.The dragon fruit juice initial concentration was standardized at 7 °Brix. After 12 hour spent in the crystallization unit,the concentration of the fruit juice increased.For the first study where the temperature of the cooling medium was remaining constant, the highest concentrated fruit juice was 17 °Brix.The best stirring rate to produce that concentrated fruit juice was 1200 rpm.For the second study where the stirring rate was remaining constant,the highest concentrated fruit juice also was 17 °Brix.The best cooling medium temperature to produce that particular concentrated fruit juice was -10 °C.As a conclusion, the highest concentrated fruit juice produced was 17 °Brix.The best stirring rate was 1200 rpm while the best cooling medium temperature was -10 °C.